Implications of Genomics in Poultry a farming enterprise - Bhattacharya, T K; Chatterjee, R N (Indian Farming, 2016)
Chicken genomics has been the first study performed among all the farm animals after initiation of Human Genome Project. Considering importance of chicken in farm livelihood, the species was selected for accomplishment of Chicken Genome project. The total genomic length of chicken is 1.2Ã—106 bp in which approximately 5,000 genes are present. The study of ESTs, global gene expression profiling etc. performed to establish metabolic pathways and functional mapping for localization of gene on the chromosome. Several genes regulate egg production and meat production in chicken and study of these genes will explore genetic markers for the traits to be further used in selection programme and to produce genetically superior animals having potential of enriched egg production/meat production/egg protein/meat protein/low egg cholesterol/low meat cholesterol etc. Genomics in poultry has bright future to augment productivity at a faster rate in poultry.